2019
DOI: 10.5812/iji.96828
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Specification of the Last Resort Polymyxins: An Intelligent Approach

Abstract: Polymyxins, especially polymyxin B and colistin (polymyxin E), are the last resort antibiotics among a few reserve antibiotics still showing potentiality against Gram-negative superbugs. Globally, during the alarming situation of fast-spreading antibiotic resistance in Gram-negative bacteria, the therapeutic application of polymyxins should be rational and target-specific considering their pharmacokinetic (PK) and pharmacodynamic (PD) characteristics. Intravenous polymyxin B shows relatively higher plasma prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Studies have reported that a relatively high polymyxin B concentration is significantly achieved in lungs’ sub-compartments after its direct aerosolised administration, and exhibits better microbial eradication compared to intravenous polymyxin B. Conversely, a single-route intravenous administration of polymyxin B in the treatment of severe pneumonia in high-risk ventilated patients of this study, was found to be less efficient in achieving microbial eradication [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 73%
“…Studies have reported that a relatively high polymyxin B concentration is significantly achieved in lungs’ sub-compartments after its direct aerosolised administration, and exhibits better microbial eradication compared to intravenous polymyxin B. Conversely, a single-route intravenous administration of polymyxin B in the treatment of severe pneumonia in high-risk ventilated patients of this study, was found to be less efficient in achieving microbial eradication [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 73%
“…The use of polymyxin B and colistin as last-line therapy in intravenous and aerosolized form in serious infections with MDR pathogens has been attributed in clinical practice over the last couple of decades [ 12 ]. In practice, in severe upper or lower respiratory tract infections, such as VAP, aerosolized polymyxins are currently more popular among the clinicians due to its outweighed therapeutic benefits over intravenous use [ 13 , 19 , 20 ]. However, clinical data related to the use of polymyxins in the treatment of PDR K. pneumoniae VAP mostly in South Asian population is limited [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colistin is the bioactive form of CMS (administration form) and following an intravenous single dose of CMS, only 20% to 25% of the total CMS is rapidly converted to colistin-base activity (CBA) in-vivo , and the major portion of the drug is excreted through kidney as unchanged from of drug [ 20 , 22 ]. Following an intravenous dose of 150 mg CBA, the maximum plasma concentration ( C max, Plasma ) of colistin ranges from 0.4 to 0.77 mg/Liter of blood [ 22 ].…”
Section: Discussionmentioning
confidence: 99%